Pengaruh Efektivitas Kepemimpinan dan Etos Kerja Terhadap Kinerja Pegawai (Pada Badan Pengelolaan Keuangan Daerah Provinsi Bengkulu) - Merta Kusuma; Tezar Arianto; Fauzan Wira Mahendra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to know the effect of leadership effectiveness and work ethic on employee performance at the Bengkulu Province Regional Financial Management Board Either partially or simultaneously. Sempel in this study were 42 employees at the Regional Financial Management Board of Bengkulu Province. In this study the researcher used quantitative methods. The data in this study were analyzed using a multiple linear regression method using IBM SPSS. simultaneously have a significant effect on employee performance. Partially, the two variables have a significant effect on employee performance. It is better if the leadership of the Bengkulu Province Financial Management Board can continue to maintain and even improve employee performance so that the goals and targets of the board can be achieved.